Epidemiology of fungaemia in Sweden: A nationwide retrospective observational survey. Issue 10 (18th July 2018) - Klingspor, Lena; Ullberg, Måns; Rydberg, Johan; Kondori, Nahid; Serrander, Lena; Swanberg, Jonas; Nilsson, Kenneth; Jendle Bengtén, Cecilia; Johansson, Marcus; Granlund, Margareta; Törnqvist, Eva; Nyberg, Anders; et al.
Summary: Objectives: To identify the epidemiology and antifungal susceptibilities of Candida spp. among blood culture isolates to identify the epidemiology and antifungal susceptibilities of Candida spp. among blood culture isolates in Sweden. Methods: The study was a retrospective, observational nationwide laboratory‐based surveillance for fungaemia and fungal meningitis and was conducted from September 2015 to August 2016. Results: In total, 488 Candida blood culture isolates were obtained from 471 patients (58% males). Compared to our previous study, the incidence of candidaemia has increased from 4.2/100 000 (2005‐2006) to 4.7/100 000 population/year (2015‐2016). The three most common Candida spp. isolated from blood cultures were Candida albicans (54.7%), Candida glabrata (19.7%) and species in the Candida parapsilosis complex (9.4%). Candida resistance to fluconazole was 2% in C. albicans and between 0% and 100%, in non‐ albicans species other than C. glabrata and C. krusei . Resistance to voriconazole was rare, except for C. glabrata, C. krusei and C. tropicalis . Resistance to anidulafungin was 3.8% while no Candida isolate was resistant to amphotericin B. Conclusions: We report an overall increase in candidaemia but a minor decrease of C. albicans while C. glabrata and C. parapsilosis remain constant over this 10‐year period.